The Cappadocian Mothers: deification exemplified in the writings of Basil, Gregory, and Gregory - Sunberg, Carla D. (James Clarke Company, Limited, 2018)
An examination of the women in the lives of the fourth-century Cappadocian Fathers, and their influential role in the emerging theology of the early church.